"I'm Going to be Successful Someday": Women's Personal Projects to Improve Their Lives, and Implications for Clarifying the Nature of Agency in Criminological Theories of Desistance. (April 2022) - Hoskins, Kayla M.
Women's agency to construct prosocial lives remains understudied in criminology. This qualitative inquiry explores the nature and outcomes of women's personal projects, which reflect their agency. In up to five interviews, 401 women on probation and parole explained efforts to improve their lives. Psychological theory on personal projects guided analysis that revealed information on project meaning and facilitators and barriers to project pursuit. Women shared a motivation to avoid trouble and establish prosocial lives. Outcomes were improved by social support and prosocial opportunities. Findings have implications for defining and analyzing agency in desistance research and for correctional responses to women.